Existence of nonnegative solutions for a fractional parabolic equation in the whole space - Kenzizi, T. (Ukrains’kyi Matematychnyi Zhurnal, 2019)
UDC 517.9 We study existence of nonnegative solutions for a parabolic problem $\dfrac{\partial u}{\partial t} = - (-\triangle)^{\frac{α}{2}}u + \dfrac{c}{|x|^{α}}u$ in $\mathbb{R}^{d}× (0, T).$ Here$0